Pendampingan Santri Berbasis Participatory Action Research Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Di Madin Al-Islah Karangrejo - Putri, Tasya Amalia; Quluby, Hakam; Fatimah, Siti; Eliyanto, Eliyanto; Ilmie, Bahrul; Subarkah, Imam (Jurnal Inovasi dan Pengabdian kepada Masyarakat (JIPMas), 2025)
This study aims to describe the process and outcomes of mentoring students in improving their ability to read the Qur’an through the Iqro method at Madrasah Diniyah Al-Islah Karangrejo. The background of this activity stems from the fact that many students still struggle with Qur’anic reading skills, particularly in terms of fluency, articulation of letters (makhraj), vowel length (mad), and the application of basic tajwid rules. The method applied was Participatory Action Research (PAR), consisting of diagnosis, planning, implementation, evaluation, and reflection. The subjects of this study were 70 students of Madrasah Diniyah Al-Islah Karangrejo, with the mentoring program conducted over one month using observation, interviews, and documentation. The results show a significant improvement in the students’ Qur’anic reading skills. In the pre-mentoring stage, only 21% (15 out of 70 students) could read fluently. After the first cycle, the percentage increased to 50% (35 students), and by the second cycle, it reached 82% (58 students). This improvement indicates that the Iqro method, supported by the sorogan approach and repeated practice, effectively corrected reading errors, enhanced understanding of basic tajwid, and fostered students’ confidence in reading before teachers and peers. In conclusion, mentoring using the Iqro method proved effective in gradually and measurably improving students’ Qur’anic reading skills. Beyond technical ability, the program also nurtured students’ motivation, discipline, and love for the Qur’an. Therefore, similar mentoring programs may serve as an inspirational model for other Islamic educational institutions.